Analysis of the Psychological Characteristics of the Audience in Contemporary Chinese Theater Space - Zhao, Shuhang (Transactions on Social Science, Education and Humanities Research, 2024)
Since the beginning of 2023, the number of theatre performances in China has increased year by year, and a new round of " theatre defense war " is about to be opened. Whether the operators can keep up with the favorable policies, take advantage of the wind, grasp the new market competition situation, and make timely market response has become a key factor. This paper focuses on the current audience viewing psychology dimension for data sampling and analysis, in order to put forward constructive suggestions. The purpose of this project research is based on the current situation investigation and data analysis, so that the theater can better optimize management in the future. By analyzing the audience ’s views and opinions on the theater, it helps the theater to make more realistic changes.